2015
DOI: 10.1007/s10995-015-1905-9
|View full text |Cite
|
Sign up to set email alerts
|

Maternity Leave Access and Health: A Systematic Narrative Review and Conceptual Framework Development

Abstract: Background Maternity leave is integral to postpartum maternal and child health, providing necessary time to heal and bond following birth. However, the relationship between maternity leave and health outcomes has not been formally and comprehensively assessed to guide public health research and policy in this area. This review aims to address this gap by investigating both the correlates of maternity leave utilization in the US and the related health benefits for mother and child. Methods We searched the peer-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 52 publications
2
51
0
Order By: Relevance
“…Also, the ANM endorses legislating in favour of extending the duration of paid maternity leave for working mothers (González de Cosío et al, ). In developed countries, an extended period of maternity leave is associated with higher exclusive breastfeeding and longer breastfeeding duration (Andres, Baird, Bingenheimer, & Markus, ; Baker & Milligan, ). Since 1952, the period of paid maternity leave in the country covers 12 weeks, but only 32% of women have an employment with social protection.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the ANM endorses legislating in favour of extending the duration of paid maternity leave for working mothers (González de Cosío et al, ). In developed countries, an extended period of maternity leave is associated with higher exclusive breastfeeding and longer breastfeeding duration (Andres, Baird, Bingenheimer, & Markus, ; Baker & Milligan, ). Since 1952, the period of paid maternity leave in the country covers 12 weeks, but only 32% of women have an employment with social protection.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding (BF) initiation has been shown to be insufficient, and mean BF duration falls under the recommended 6-month duration in most developed countries, despite its acknowledged benefits and public health actions [1]. Among several determinants, increasing attention has been paid to return to work (RTW) as a major constraint to initiate and continue BF [2][3][4]. Numerous previous studies consistently concluded that RTW before 12-16 weeks, compared with later or not at all, was associated with shorter BF duration [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, women who planned to work after giving birth often did not begin BF, by anticipation. However, conclusions between studies are inconsistent [2,7,[11][12][13][23][24][25][26][27]. Methodological weaknesses, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the rate of sudden infant death syndrome is reduced by over onethird. 13 Benefits of breastfeeding to the mother include earlier return to prepregnancy weight and decreased risk of breast and ovarian cancers. 14 Parental leave for the nonbirth parent is less well studied, and policies are less standardized across all industries.…”
Section: Introductionmentioning
confidence: 99%